Practice of pulmonary rehabilitation - Aniket Mondal; Jitendra K. Bairwa; Madhur Joshi; Sheetu Singh (The Journal of Association of Chest Physicians)
Pulmonary rehabilitation encompasses a set of well structured, patient centric techniques aimed at enabling individuals with chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD) and bronchiectasis to take control of the trajectory of their illness by self-adjustable maneuvers to prevent and manage acute symptoms. It starts with an assessment of a patient’s baseline physical, physiological, and psychosocial status followed by educating patients and their caregivers of the natural course of the disease and encourages them to participate in care of self or their wards by better understanding of premonitory signs and symptoms and seeking timely intervention. The program then proceeds to follow a sequence of training exercises of respiratory and limb muscles to take active steps to avert distressing symptoms such as breathlessness and fatigue. Smoking cessation, nutritional assessment, and vaccination also form a part of a comprehensive rehabilitation program. If followed diligently during hospitalization and at home, pulmonary rehabilitation can significantly improve the quality of life in patients with chronic lung diseases.